2020
DOI: 10.1021/acs.iecr.0c04709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Different Hybrid Life Cycle Assessment Methodologies: A Review and Case Study of Biomass-based p-Xylene Production

Abstract: Two common life cycle assessment (LCA) methods are process LCA and economic input–output LCA, which suffer from truncation error and aggregation error, respectively. Many hybridization techniques are developed to improve the accuracy of analysis by combining both methods. This work aims to review different hybrid LCA methodologies under various data availabilities through a case study of two biomass-based p-xylene production technologies using concentrated acid (CA) and molten salt hydrate (MSH) hydrolysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 111 publications
(310 reference statements)
0
11
0
Order By: Relevance
“…Specifically, Υ i,j that correspond to the expenditures of each of the commodities i to produce one physical unit of the new-commodity in each of the new industries j are required. Then, future use, in monetary terms, follows Equation (9). It is assumed that the new industries do not use the new commodity as input.…”
Section: Use Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Υ i,j that correspond to the expenditures of each of the commodities i to produce one physical unit of the new-commodity in each of the new industries j are required. Then, future use, in monetary terms, follows Equation (9). It is assumed that the new industries do not use the new commodity as input.…”
Section: Use Tablementioning
confidence: 99%
“…The underlying models for LCA, life cycle inventory (LCI) models, may be constructed using traditional process-based LCI [5], environmentally extended input-output-based LCI [5][6][7] or hybrid approaches that integrate the two [5,8,9]. As EEIO models (also known as Input-Output LCA models) embed the full structure of the underlying economy represented in the input-output table, EEIO models have an inherent advantage of comprehensiveness and completeness when it is of interest to understand the impacts of new products and new technologies across the whole economy.…”
Section: Introductionmentioning
confidence: 99%
“…35 Readers may find a review and application of the hybrid LCA methodology for comparing two biomass-based pxylene productions useful. 36 It should be recognized that chemical process design technoeconomic analysis (TEA) and LCA are usually performed at a low technology readiness level (TRL) based on the prevalent efficiencies of the unit operations, such as process yields and separations. Prospective LCA builds on current LCA projections to project future process and product improvement scenarios, 37 thereby providing a trajectory for current technologies to improve sustainability attributes.…”
Section: ■ Life Cycle Assessment Approaches For Catalytic Processesmentioning
confidence: 99%
“…In such cases, the economic input–output LCA (EIO-LCA) method based on economic activities and their environmental impacts may be useful. , A hybrid LCA method that combines the advantages of process LCA and EIO-LCA methods has also been employed and helps further delineate the upstream impacts from the gate-to-gate impacts . Readers may find a review and application of the hybrid LCA methodology for comparing two biomass-based p -xylene productions useful …”
Section: Life Cycle Assessment Approaches For Catalytic Processesmentioning
confidence: 99%
“…Therefore, numerous combined methods are utilized to ameliorate the total accuracy. Luo and Ierapetritou [109] examined numerous integrated LCA methods over a case study of two biomass-based p-xylene fabrication techniques and suggested essential insights appropriate to future LCA. Moreover, LCAs of the production of broadly employed titanium dioxide nanoparticles [110] and butyl acetate [111] furnished conceptual directing for more sustainable synthesis of both.…”
Section: Life-cycle and Systems Thinkingmentioning
confidence: 99%